Gambaran Tingkat Pengetahuan tentang Period After Opening (PAO) dan Perilaku Penyimpanan Kosmetika Perawatan pada Remaja di Kota Tangerang: The Level of Knowledge about Period After Opening (PAO) and Storage Behavior of Cosmetics in Adolescents in Tangerang - Yopi Septianingrum; Ulya Safrina; Nanda Puspita; Surahman Surahman (Jurnal Sains dan Kesehatan, 2023)
Period After Opening (PAO) is the time limit for using cosmetics after the packaging is opened. Information about PAO is different from the expiration date of cosmetic products. This information is generally contained in cosmetic packaging to ensure quality and safety. This study aimed to describe the knowledge level about the Period After Opening (PAO) and cosmetic storage behavior in adolescents in RW 02 Gondrong Village, Cipondoh District, Tangerang City, in 2022. This research uses a quantitative descriptive survey method. The sampling technique in this study was random cluster sampling followed by 91 respondents. Data collection was carried out using a questionnaire. The data analysis used was univariate. Based on the study results, most respondents were aged 16-18 years, with 45 respondents (49.5%) and high school/MA/equivalent education (37.4%). Most of them use cleaning cosmetics, with 44 respondents (48.4%). As many as 77 respondents (84.6%) used ready-made products (non-concoctions), and 51 respondents (56.0%) bought them at a price range of IDR 50,000 - IDR 200,000. Most respondents store skincare at room temperature, with 66 respondents (72.5%). In this study, the majority of respondents, namely 75 people (82.4%), stated that there was no PAO information on brochures or cosmetic packaging. Nonetheless, more than half of the respondents had good knowledge of PAO, with 51 respondents (56.0%). Knowledge of PAO in cosmetics is essential to guide the safe use of cosmetics for consumers, especially teenagers. Keywords: Cosmetics, knowledge, Period after Opening (PAO) Abstrak Period After Opening (PAO) adalah batas waktu penggunaan kosmetik setelah kemasan kosmetik dibuka, dimana produk masih aman digunakan. Tujuan dari penelitian ini adalah mengetahui gambaran tingkat pengetahuan tentang Period After Opening (PAO) dan perilaku penyimpanan kosmetika pada remaja di RW 02 Kelurahan Gondrong Kecamatan Cipondoh Kota Tangerang tahun 2022. Penelitian ini menggunakan metode survei deskriptif kuantitatif. Teknik pengambilan sampel dalam penelitian ini yaitu cluster random sampling dan diikuti oleh 91 responden. Pengumpulan data dilakukan dengan menggunakan kuesioner. Analisis data yang digunakan berupa analisis univariat. Berdasarkan hasil penelitian diketahui bahwa, mayoritas responden berusia 16 – 18 tahun sejumlah 45 responden (49,5%) dan lebih dari separo responden memiliki pengetahuan yang baik dengan jumlah 51 responden (56,0%). Mayoritas responden menggunakan kosmetika pembersih dengan jumlah 44 responden (48,4%), jenis sediaan skincare produk yang sudah jadi atau non racikan dengan jumlah 77 responden (84,6%), dan mayoritas responden membeli skincare dengan kisaran harga Rp 50.000 - Rp 200.000. Pada penelitian ini dijelaskan, bahwa mayoritas responden tidak memiliki skincare yang terdapat informasi PAO pada brosur atau kemasannya dan mayoritas responden menyimpan skincare pada ruang kamar dengan jumlah 66 responden (72,5%). Kata Kunci: Kosmetika, Pengetahuan, Period after Opening (PAO)